2006
DOI: 10.1002/pmic.200600463
|View full text |Cite
|
Sign up to set email alerts
|

Proteome profiles of mucosal immunoglobulin uptake in inflamed porcine gut

Abstract: Acquisition of passive immunity by endocytosis of intact immunoglobulins (Ig) from colostrum is critical for prevention of intestinal and systemic diseases in neonatal mammals. We compared proteome patterns of healthy and inflamed gut tissues from pre-term piglets to investigate the effect of inflammation on acquisition of passive immunity. A clear difference in the two-dimensional gel electrophoresis protein patterns between healthy and inflamed intestinal tissues was observed, suggesting that inflamed tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…Nonselective Uptake of Intact Proteins and Selective Uptake of IgG During Suckling-Enterocytes in proximal small intestine of suckling rodents direct active, receptor-mediated endocytosis and transcytosis of IgG from maternal milk, helping the newborn animals to acquire passive immunity (38,39). This highly selective uptake of IgG is mediated by the neonatal Fc receptor (IgG receptor FcRn) at the apical surface of the epithelial cells.…”
Section: Establishment Of Label-free Quantitative Proteomics Of In-mentioning
confidence: 99%
“…Nonselective Uptake of Intact Proteins and Selective Uptake of IgG During Suckling-Enterocytes in proximal small intestine of suckling rodents direct active, receptor-mediated endocytosis and transcytosis of IgG from maternal milk, helping the newborn animals to acquire passive immunity (38,39). This highly selective uptake of IgG is mediated by the neonatal Fc receptor (IgG receptor FcRn) at the apical surface of the epithelial cells.…”
Section: Establishment Of Label-free Quantitative Proteomics Of In-mentioning
confidence: 99%
“…A 2DE based study of colostrum protein uptake in neonatal gut demonstrated that inflammation of the gut epithelium greatly impaired uptake of immunoglobulins from maternal colostrum [78]. A more recent work aimed to characterize in more details which specific colostrum protein components could be traced within the intestinal tissues of neonatal piglets after 24 h of natural suckling.…”
Section: The Role Of Nutritional Factorsmentioning
confidence: 98%
“…A number among the rather few mass spectrometry-based in vivo proteomic studies in the context of intestinal inflammation have been performed by the Bendixen team, using the omnivore piglet as a model: for example, they compared proteome patterns of healthy and inflamed gut tissues harvested from preterm piglets to investigate the effect of inflammation on acquisition of passive immunity (Danielsen et al, 2006). The molecular differences in the 2DE protein patterns between healthy and inflamed intestinal tissues suggested that inflamed tissues fail to absorb and transfer Ig from colostrum to epithelial cells.…”
Section: Proteomics In Intestinal Immunitymentioning
confidence: 99%